À La Recherche De L'Espace Perdu: Architecture, Urban Fabric, and French Travelers to Antioch (1784–1914). Issue 1 (16th November 2016) - Açıkgöz, Ümit Fırat
Abstract : Ottoman Antioch, a marginalized outpost by the late 18th century, attracted French travelers thanks to its illustrious Roman, Early Christian, and crusader histories. To make sense of the city, these travelers relied either on previous travelogues or on their own observations of the built environment. This article sheds light on the inter-textual relationship among travelogues, and on how both the built environment of Ottoman Antioch and representations of the pre-Islamic city and its monuments shaped the travelers' narratives. The dramatic contrast between the insignificance of Ottoman Antioch and the grandeur of the pre-Islamic city prompted the travelers to reflect on the glories of Greco-Roman antiquity and the 'decadence of the Oriental civilizations'. I focus on four French travelers who visited Antioch between 1780 and 1914, and argue that they turned the state of the city's architecture and urban fabric into a critical tool to imagine their historical connections to the region, reproduce the Orientalist stereotypes in circulation in Europe at the time, and, thereby setting the tone for the colonization of the region.